A negative electrode additive using sugar-derived carbon material SG as a carbon source, a negative electrode plate for a lead-carbon battery, and a preparation process for the negative electrode plate
By using sugar-derived carbon material SG as the negative electrode additive in lead-carbon batteries, the problem of battery performance degradation caused by hydrogen evolution is solved, and the efficient cycle of the battery and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202410951126.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-07-16
AI Technical Summary
Existing lead-carbon batteries have hydrogen evolution during discharge and charging, resulting in water loss, reduced charging efficiency and reduced performance of the batteries.
Using a negative electrode additive with a sugar-derived carbon material SG as the carbon source, an SG carbon material with high conductivity and specific surface area is prepared by high-temperature calcination, and mixed it with a semi-finished product of lead paste for the preparation of a negative electrode plate of lead carbon battery.
It effectively inhibits the hydrogen evolution reaction, reduces the sulfation of the negative electrode, improves the cycle life and electrochemical performance of the battery, and has no environmental pollution in the process and is cheap.
Smart Images

Figure CN118919722B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery energy storage, and in particular to a negative electrode additive using a sugar-derived carbon material SG as a carbon source, a lead-carbon battery negative electrode plate, and a preparation process of the negative electrode plate. Background Art
[0002] Irreversible sulfation of the negative electrode of lead-acid batteries is the main reason for the failure of batteries under HRPSoC and low temperature conditions. By adding carbon materials to the negative electrode active material to make a "lead-carbon battery", the battery performance is greatly improved. Commonly used additives include activated carbon, graphite, carbon nanotubes, and graphene. Therefore, adding carbon materials to the negative electrode active material can improve the failure time of lead-acid batteries and extend the cycle life of the battery.
[0003] Lead-carbon battery is a new type of double-layer capacitor battery between supercapacitors and traditional lead-acid batteries. It combines the common advantages of supercapacitors and lead-acid batteries. It has the advantages of supercapacitors' large capacity and lead-acid batteries' long cycle life. Lead-carbon batteries have attracted widespread attention due to their low cost and relatively stable performance under high-rate charge and discharge conditions. Among them, various carbon materials such as graphite, activated carbon, carbon black, and rice husk-based porous carbon have been used as additives for lead-acid batteries.
[0004] However, since the working potential of the carbon material is very different from that of the lead negative electrode, if the two are combined in a system, during the discharge process, most of the discharge current comes from the lead negative electrode, and during charging, the carbon material will be charged first than the lead negative electrode. More seriously, since the hydrogen evolution potential of the carbon material itself is relatively low, when the battery reaches the end of charging, very serious hydrogen evolution will occur on the carbon material, causing serious water loss in the battery, reducing the battery's charging efficiency, and greatly affecting the battery's performance.
[0005] Chinese patent application CN102024946A discloses a super lead-acid battery plate active material, wherein the components and mass ratio of the positive electrode active material are: lead powder 100, conductive fiber 0.01-2, metal oxide 0.1-5, conductive carbon material 0.1-2, sodium carboxymethyl cellulose 0.01-1, dilute sulfuric acid 1-15; the components and mass ratio of the negative electrode active material are: lead powder 100, conductive fiber 0.01-2, conductive carbon material 0.1-5, barium sulfate 0.1-0.6, humic acid 0.2-1, lignin 0.01-0.1, dilute sulfuric acid 1-15. On the basis of adding a variety of carbon materials to the lead paste, the purpose of hydrogen inhibition is achieved by adding one or more combinations of metal oxides: tin oxide, bismuth oxide, and cerium oxide. However, this simple mechanical stirring makes it difficult to mix the hydrogen evolution inhibitor with the lead paste evenly, so the hydrogen evolution inhibitor is difficult to play its role in inhibiting hydrogen.
[0006] Chinese patent application CN102306784A proposes to load the hydrogen evolution inhibitor onto activated carbon by ball milling or solvent precipitation, so that the modified activated carbon hydrogen evolution overpotential is increased, thereby significantly improving the cycle performance of the battery. It uses a simple chemical deposition method to load the hydrogen evolution inhibitor on the surface of the carbon material, but it is impossible to load the hydrogen evolution inhibitor evenly on the carbon material by a simple impregnation and precipitation method, which makes the hydrogen evolution inhibitor unable to play a good role in suppressing hydrogen. Moreover, the particle size of the load obtained by this method is too large, and it is very easy to accumulate and agglomerate. Such additives will affect the battery performance instead and fail to achieve the desired purpose.
[0007] Therefore, it is very necessary to develop a negative electrode additive, a lead-carbon battery negative electrode plate and a preparation process of the negative electrode plate using sugar-derived carbon material SG as a carbon source that can solve the above technical problems. Summary of the invention
[0008] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a negative electrode additive with sugar-derived carbon material SG as a carbon source, a lead-carbon battery negative electrode plate, and a preparation process of the negative electrode plate, which are free of environmental pollution, have a long battery cycle life, and good electrochemical performance. The present invention applies the negative electrode additive with sugar-derived carbon material SG as a carbon source to the negative electrode plate of the lead-carbon battery, which reduces the sulfation of the negative electrode and inhibits the hydrogen evolution reaction. The present invention uses sugar, which is free of environmental pollution and low in price, as a carbon source and directly calcines it at high temperature to obtain a carbon material.
[0009] The present invention is achieved through the following technical solutions:
[0010] A negative electrode additive using a sugar-derived carbon material SG as a carbon source comprises the following components by weight percentage: 0.5-3 parts of the sugar-derived carbon material SG and 97-99.5 parts of a semi-finished lead paste.
[0011] The sugar-derived carbon material SG is a carbon material obtained by pyrolyzing sugar and then doping it with nitrogen, and may also be referred to as a sugar-derived nitrogen-doped carbon material.
[0012] Preferably, the mass percentage of the sugar-derived carbon material SG in the negative electrode additive is 0.1%-3%.
[0013] Preferably, the method for preparing the sugar-derived carbon material SG comprises the following steps:
[0014] (1) taking sugar and soaking it in an acid solution, washing it with water, drying it, and grinding it to obtain pretreated sugar;
[0015] (2) The pretreated sugar is mixed with ammonium chloride, heated, cooled, and ground into powder.
[0016] The sugar-derived carbon material SG prepared by the present invention is a SG carbon material that tends to graphitize. The SG carbon material has the advantages of simple preparation, low raw material price, stable chemical properties and environmental protection. The SG carbon material can increase the conductivity of the lead-carbon battery and provide a large specific surface area and chemical reaction activity.
[0017] More preferably, the sugar in step (1) includes but is not limited to at least one of glucose, chitosan and edible white sugar.
[0018] More preferably, the acid in step (1) comprises at least one of oxalic acid and hydrochloric acid.
[0019] The purpose of soaking the sugar in the acid solution in step (1) is to remove substances on the surface of the sugar.
[0020] More preferably, the mass ratio of sugar to acid solution is 1-3:5.
[0021] More preferably, the mass concentration of the acid solution is 2-4%.
[0022] More preferably, the soaking time is 1-2 hours.
[0023] The water used for washing in step (1) is ultrapure water.
[0024] More preferably, the drying method is vacuum drying. The vacuum drying can be performed in a vacuum drying oven.
[0025] More preferably, the drying temperature is 40-60° C. and the drying time is 12-24 h.
[0026] More preferably, step (1) comprises the following steps:
[0027] Take sugar and add it to a 2-4wt% acid solution and soak it for 1-2h, the mass ratio of sugar to acid solution is 1-3:5, wash with water, vacuum dry, the drying temperature is 40-60℃, the drying time is 12-24h, grind, and obtain pretreated sugar. The pretreated sugar is light yellow powder.
[0028] More preferably, the mass ratio of the pretreated sugar to ammonium chloride in step (2) is 1:0.5-2, and further preferably 1:1.
[0029] The pretreated sugar in step (2) is mixed with ammonium chloride and stirred for 5-15 minutes.
[0030] More preferably, the heating temperature in step (2) is 1000-1200°C and the heating time is 3-4h. The heating operation can be performed in a N2 gas tube furnace. Sugars can be used to obtain sugar-derived carbon materials SG with different graphitization degrees by controlling the different calcination temperatures.
[0031] More preferably, step (2) also includes, before heating, heating to 200-400°C at a rate of 2-4°C / min and keeping the temperature for 60-120 min.
[0032] More preferably, the cooling temperature in step (2) is below 40°C, and further preferably room temperature to 40°C.
[0033] More preferably, step (2) comprises the following steps:
[0034] Mix the pretreated sugar and ammonium chloride in a mass ratio of 1:1, first heat to 200-400℃ at a rate of 2-4℃ / min, keep warm for 60-120min, then heat to 1000-1200℃, heat for 3-4h, cool to below 40℃, and grind into powder. After cooling, a black expanded product is obtained. The grinding operation can be carried out in an agate mortar. After grinding, a black powder is obtained.
[0035] Preferably, the semi-finished lead paste comprises the following components in parts by weight: 0.05-0.1 parts of lignin, 0.2-0.4 parts of humic acid, 0.05-0.2 parts of fiber, 0.5-2.5 parts of barium sulfate and 97-99 parts of lead powder.
[0036] More preferably, the fiber includes at least one of polypropylene fiber, polyacrylonitrile fiber, composite conductive fiber, carbon fiber, polyacetylene fiber, polyaniline fiber, polypyrrole fiber and polyester fiber.
[0037] The present invention also relates to a lead-carbon battery negative electrode plate, comprising the negative electrode additive mentioned above.
[0038] The present invention also relates to a process for preparing the above-mentioned lead-carbon battery negative plate, comprising the following steps:
[0039] S1: mixing the sugar-derived carbon material SG and the semi-finished lead paste, adding water, and stirring to obtain a mixture;
[0040] S2 is to coat the mixture on the negative electrode grid, flatten it, spray it with acid, solidify it, and dry it.
[0041] Preferably, in step S1, the mass ratio of water to sugar-derived carbon material SG is 0.05-0.15:1; and step S1 is performed by stirring in a paste mixer.
[0042] Preferably, sulfuric acid is used for acid leaching in step S2, and the density of sulfuric acid is 1.23-1.28 g / mL. After acid leaching, the plate is left to stand in the air for 4 hours, and then dried in a constant temperature and humidity chamber. After the negative electrode plate is completely dried, a sealed battery can be prepared.
[0043] In step S2, the mixture is coated on the negative electrode grid. The weight of the negative electrode plate is about 17.0-17.5 g, and the amount of paste applied to a small piece of negative electrode plate is 42.5 g.
[0044] The beneficial effects of the present invention are:
[0045] (1) The sugar-derived carbon material SG of the present invention has the characteristics of low material price, simple preparation process, and low requirements for equipment. SG carbon materials with different degrees of graphitization can be obtained by controlling the different calcination temperatures of sugars.
[0046] (2) The present invention can obtain sugar-derived carbon materials SG with different morphologies by controlling different calcination temperatures.
[0047] (3) The sugar-derived carbon material SG of the present invention is used for the first time in lead-carbon batteries due to its good conductivity and high specific surface area, and exhibits relatively excellent electrochemical performance.
[0048] (4) Compared with traditional lead-carbon batteries, the present invention has better electrochemical performance and longer cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 X-ray diffraction (XRD) patterns of the SG carbon material prepared in Example 1 and the activated carbon AC used in Comparative Example 1.
[0050] Figure 2 This is a scanning electron microscope (SEM) image of the SG carbon material prepared in Example 1.
[0051] Figure 3 The Tafel diagrams of the negative electrode plates prepared in Examples 1-5 and Comparative Example 1.
[0052] Figure 4 Raman spectra of the SG carbon material prepared in Example 1 and the activated carbon AC used in Comparative Example 1.
[0053] Figure 5 This is the adsorption-desorption curve of the SG carbon material prepared in Example 1.
[0054] Figure 6 This is the pore size distribution diagram of the SG carbon material prepared in Example 1.
[0055] Figure 7 This is the cyclic voltammetry (CV) diagram of the negative electrode plate with SG as the carbon source prepared in Example 1.
[0056] Figure 8 This is the cyclic voltammetry (CV) diagram of the SG negative electrode plate prepared in Example 2.
[0057] Fig. 9This is the cyclic voltammetry (CV) diagram of the SG negative electrode plate prepared in Example 3.
[0058] Fig.10 This is the cyclic voltammetry (CV) diagram of the SG negative electrode plate prepared in Example 4.
[0059] Fig.11 This is the cyclic voltammetry (CV) diagram of the SG negative electrode plate prepared in Example 5.
[0060] Fig.12 This is the cyclic voltammogram (CV) of the negative electrode plate in comparative example 1 with AC as the additive.
[0061] Fig.13 This is the cyclic voltammetry (CV) diagram of the blank negative electrode plate of Comparative Example 2.
[0062] Fig.14 The linear cyclic voltammetry (LSV) diagrams of the negative plates of Example 1, Comparative Example 1 and Comparative Example 2 are shown.
[0063] Fig.15 These are the electrochemical impedance spectroscopy (EIS) graphs of the negative plates of Example 1, Comparative Example 1, and Comparative Example 2.
[0064] Fig.16 This is the X-ray photoelectron spectrum (XPS) diagram of the SG carbon material prepared in Example 1, which includes the full spectrum, C 1s, N 1s, and O 1s spectrum from top to bottom.
[0065] Fig.17 The graphs are the relationship between the cycle life and voltage of Examples 1-5 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0066] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.
[0067] The sugar-derived carbon material SG of the present invention may also be referred to as an SG carbon material.
[0068] The fibers in the following embodiments are short polypropylene fibers, model: JH high-strength fiber, purchased from Shandong Jinkeli Power Technology Co., Ltd.
[0069] Example 1
[0070] A negative electrode additive material using a sugar-derived carbon material SG as a carbon source, which contains, by weight percentage, 1% of the sugar-derived carbon material SG and 99% of a uniformly mixed lead paste semi-finished product.
[0071] The semi-finished lead paste product comprises the following components in parts by weight: 0.05 parts of lignin, 0.2 parts of humic acid, 0.05 parts of fiber, 0.5 parts of barium sulfate and 97 parts of lead powder.
[0072] The preparation process of the sugar-derived carbon material SG comprises the following steps:
[0073] (1) 30 g of chitosan was soaked in 50 g of 2% oxalic acid solution for 1 h, washed with ultrapure water, placed in a vacuum drying oven at 60° C. for 12 h, and ground into light yellow powder to obtain pretreated chitosan.
[0074] (2) 10 g of pretreated sugar was mixed with 10 g of ammonium chloride, stirred for 10 min, heated to 400 °C at a rate of 2 °C / min, kept warm for 60 min, heated to 1100 °C in a N2 gas tubular furnace, kept warm for 3 h, cooled to room temperature, collected the black expanded product, and ground into black powder in an agate mortar to obtain the sugar-derived carbon material SG.
[0075] The preparation process of the semi-finished lead paste product is as follows:
[0076] Add all components into a large mixer, add 50% sulfuric acid, the mass ratio of lead powder to sulfuric acid is 100g:30g, and stir until the density is 4.28g / mL.
[0077] The negative plate preparation process includes the following steps: S1: mixing the sugar-derived carbon material SG with the semi-finished lead paste, adding a small amount of deionized water, the mass ratio of the deionized water to the sugar-derived carbon material SG being 0.15:1; adding the mixture into a paste mixing machine and stirring to obtain a mixture;
[0078] S2 coated the mixture on the negative electrode grid (the mass of the negative electrode grid was 17.5 g), the mass of the mixture was 42.5 g, the negative electrode grid was flattened, acid was irrigated with H2SO4 with a density of 1.25 g / mL, and then placed in a constant temperature and humidity chamber for curing and drying to obtain a negative electrode plate.
[0079] Example 2
[0080] The only difference compared with Example 1 is that the amount of sugar-derived carbon material SG used is 0.5%.
[0081] Example 3
[0082] The only difference compared with Example 1 is that the amount of sugar-derived carbon material SG used is 0.75%.
[0083] Example 4
[0084] The only difference compared with Example 1 is that the amount of sugar-derived carbon material SG used is 1.5%.
[0085] Example 5
[0086] The only difference compared with Example 1 is that the amount of the sugar-derived carbon material SG is 3%.
[0087] Comparative Example 1
[0088] The only difference compared with Example 1 is that one part of the sugar-derived carbon material SG is replaced with an activated carbon (AC) material of the same mass.
[0089] Comparative Example 2
[0090] The only difference compared with Example 1 is that one part of the sugar-derived carbon material SG is replaced with an equal mass of Pb paste material.
[0091] Example 1
[0092] (1) In order to determine the crystal structure of the sample, the sugar-derived carbon material SG prepared in Example 1 (hereinafter referred to as SG carbon material) and the activated carbon (AC) material of Comparative Example 1 were subjected to XRD test. The results are as follows: Figure 1 As shown in the figure: The two broad peaks of SG carbon material at 23° and 43° respectively represent the (002) and (101) lattice planes of graphite crystals, and both broad peaks represent the amorphous structure of carbon. The (002) peak of SG material is sharper, indicating that the degree of graphitization of SG carbon material is higher than that of AC. This shows that the carbon in SG carbon material gradually develops into graphitized carbon after high-temperature heat treatment, and a part of graphite phase is generated.
[0093] (2) The SG carbon material prepared in Example 1 was subjected to SEM testing. Figure 2 As shown, the SG carbon material has abundant protrusions, grooves and corrugated structures, and the enlarged protrusion surface is full of sand dune-like textures. This is due to the spontaneous and stress-induced thermodynamic relaxation of the sugar precursor during heating, and the thermodynamic fluctuations caused by impurities in the precursor. This structure achieves a high specific surface area and improves the electrochemical performance of the negative plate.
[0094] (3) The negative electrode plates prepared in Examples 1-5 and Comparative Example 1 were subjected to Tafel curve tests. Figure 3 As shown, the absolute value of the Tafel slope of Example 1 is almost the smallest, and the degree of hydrogen evolution is also almost the smallest. This shows that the carbon material prepared in Example 1 increases the hydrogen evolution overpotential and inhibits the occurrence of hydrogen evolution reaction to the greatest extent.
[0095] (4) Raman spectroscopy was performed on the SG carbon material prepared in Example 1 and the activated carbon (AC) material of Comparative Example 1. Figure 4 As shown, 1335cm -1 The D band at 1588cm is a disordered band, indicating the crystal defects of carbon atoms, corresponding to SP3 carbon, while the-1 The G band at is related to the vibration of the graphite lattice, indicating sp2 carbon. The relative ratio of the D band to the G band represents the degree of disorder of carbon. The ID / IG of SG (0.42) is lower than that of AC (0.99). The SG carbon material has a higher degree of graphitization. The greater the degree of graphitization of carbon in the battery plate, the stronger the electron conduction ability and the better the cycle efficiency of the battery.
[0096] (5) The SG carbon material prepared in Example 1 was subjected to BET test, and the adsorption-desorption curve was as follows: Figure 5 As shown, the specific surface area and pore volume of SG are 404.36 m 2 / g and 0.04cm 3 / g. The adsorption-desorption curve of SG is a typical type IV isotherm, and the line begins to steepen at low pressure (P / P 0 =0.2), indicating that the SG carbon material has a large number of micropores and mesoporous structures. However, its hysteresis loop is not obvious, indicating that the micropores dominate the pore structure. The pore size distribution of the SG carbon material is shown in Figure 6 As shown, the pore size distribution peak of SG is between 0 and 10 nm, which is consistent with the corresponding N2 adsorption-desorption curve.
[0097] (6) The SG carbon material prepared in Example 1 was subjected to XPS testing. Fig.16 As shown, the surface chemical properties of SG carbon materials were determined. XPS spectra show the presence of N, C, and O elements in the sample. In the N1s spectrum, there is a very obvious peak at around 399eV, corresponding to the bonding type of NC, and a small peak at 403eV, corresponding to N 3- In the O1s spectrum, only the peak at 532 eV appears, which corresponds to the presence of CO. In the C1s spectrum, the peak at 284 eV corresponds to graphitic carbon, and the small peak at 285 eV corresponds to elemental carbon (CC).
[0098] (7) Examples 1-5, Comparative Example 1, and Comparative Example 2 were used as working electrodes, Hg / Hg2 SO4 was used as reference electrode, and Pt was used as counter electrode to form a three-electrode system for electrochemical testing of the negative electrode. The electrolyte was 1.28 g / ml H2SO4, the scan rate range was -1.2--0.2 V, and the scan rate was 0.01 V / s. The spectra obtained in Examples 1-5 and Comparative Example 1-2 corresponded to Figure 7-Figure 13 In Example 1, the amount of SG carbon material used is 1%. Figure 7 1 part of SG is represented in the figure, and the same applies to other embodiments and comparative examples. Fig.13 , recorded as blank (blank control).
[0099] The specific capacitance is calculated according to the formula, which is as follows:
[0100]
[0101] In the formula, Cs is the specific capacitance, S is the scan rate in the cyclic voltammetry test, A is the rectangular area in the cyclic voltammetry curve, ΔV is the scan voltage range, and m is the mass of the active substance of the carbon material.
[0102] The calculated results of specific capacitance are shown in Table 1.
[0103] Table 1
[0104]
[0105] Figure 7-Figure 13 In the CV diagram, the anode peak corresponds to the charging process, and the cathode peak corresponds to the discharging process. As the SG addition content continues to increase, the cathode peak and the anode peak intensity continue to increase. When the SG addition content is 1%, the electrode plate has the strongest anode peak and cathode peak, and the overlap between the cathode peak and the anode peak is the highest, indicating that its cycle performance is better. The capacity of the 1% SG electrode plate is much larger than that of the other groups of electrode plates, 5.75 times that of the blank group and 1.56 times that of the AC group. This shows that the utilization rate of active materials on the negative electrode plate with 1% SG is higher and the electrochemical performance is the best.
[0106] The LSV diagrams of Example 1 and Comparative Examples 1-2 measured by the three-electrode system are as follows: Fig.14 As shown in Figure 2 (Comparative Example 2 is Blank), at a voltage of -1.1V, the negative plate with a content of 1% SG has the highest hydrogen evolution potential and the worst hydrogen evolution ability, reaching -0.028A / cm 2 The starting potential of hydrogen evolution in the group with 1% SG, 1% N, P / RC and blank was 1% SG < blank group < 1% AC. As the scanning voltage gradually moved to a low voltage, the hydrogen evolution current also gradually decreased from a stable state, and the electrode plate began to evolve hydrogen. The 1% SG electrode plate had the lowest starting potential for hydrogen evolution, and the hydrogen evolution reaction started the latest, and HER was effectively suppressed.
[0107] Example 1 and Comparative Examples 1-2 were measured by a three-electrode system, and the EIS diagram obtained by simulating the equivalent circuit diagram of the lead-carbon battery is shown in Figure 15, showing a high-frequency loop and a low-frequency curve. In the high-frequency region, it can be seen that the diameter of the semicircle first decreases and then increases with the increase in the amount of SG added. This capacitive contribution is related to the contact between carbon ions. The semicircle diameter of the 1% SG negative plate is the smallest, which indicates that the conductivity of the 1% negative plate is maximized after adding SG. In the low-frequency region, the spectrum shows obvious linear behavior. The material transfer diffusion rate in the pores of the electrode plate is the determining factor in the low-frequency range. Therefore, the difference in the impedance spectrum angle means that these electrode plates have different pore structure parameters.
[0108] The fitting data of Examples 1-5 and Comparative Examples 1-2 are shown in Table 2. Rs is the ohmic resistance of the electrode plate. The smaller the Rs value, the better the conductivity of the electrode plate. The Rs value of the 1% SG electrode plate is much smaller than that of the blank group (Comparative Example 2) and the AC group (Comparative Example 1) electrode plate, indicating that the addition of carbon increases the conductivity of the negative electrode plate, and when the SG carbon material content is 1%, the Rs value is the smallest and the electrode plate has the best conductivity. f and R f They correspond to the non-ideal double-layer capacitance of the carbon material and the corrosion resistance of the NAM and lead grid in the electrode plate. The value of charge transfer resistance Rct is usually used to compare the size of kinetic activity, and the Rct value is inversely proportional to the kinetic activity. In Table 2, the Rct values of the SG group electrode plates are all smaller than those of the CB group and the blank group electrode plates, showing stronger kinetic activity. Q dl It represents the non-ideal electrical layer capacitance of NAM, and its value is proportional to the electrochemically effective area of the electrode plate. The electrochemically effective active area of the 1% SG electrode plate is more prominent, which is related to the larger specific surface area of the SG carbon material.
[0109] Table 2
[0110]
[0111] Examples 1-5 and Comparative Examples 1 and 2 were prepared into closed simulated batteries, formed, and the cycle life of the batteries was tested. Fig.17 The results show that the cycle numbers of the blank battery and 1% SG under HRPSoC operation are 809 and 4324 respectively, proving that the addition of SG composite material increases the cycle life of the battery and the cycle life is the longest when the content is 1%.
[0112] The test process of the simulated battery is as follows:
[0113] Chemical process:
[0114] (1) 0.5C constant current charging for 1h;
[0115] (2) Leave for 20 seconds;
[0116] (3) 1C constant current charging for 20h;
[0117] (4) Leave for 20 seconds;
[0118] (5) 1C constant current discharge for 1h;
[0119] (6) Leave for 20 seconds;
[0120] (7) 1C constant current charging for 10h;
[0121] (8) Leave for 20 seconds;
[0122] (9) 2C constant current discharge for 1h;
[0123] (10) Leave for 20 seconds;
[0124] (11) 1C constant current charging for 4h;
[0125] (12)End.
[0126] Cycle test process:
[0127] (1) 0.1C constant current charging to the upper limit voltage of 2.4V;
[0128] (2) Leave for 5 minutes;
[0129] (3) 2.4V constant voltage charging for 10h;
[0130] (4) Leave for 5 minutes;
[0131] (5) 1C constant current discharge for 1h;
[0132] (6) Leave for 10 minutes;
[0133] (7) 2C constant current charging for 60s;
[0134] (8) Leave for 10 seconds;
[0135] (9) 2C constant current discharge for 60s;
[0136] (10) Leave for 10 seconds;
[0137] (11) Repeat (8)-(10) until the lowest voltage reaches 1.7V.
[0138] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A negative electrode additive using sugar-derived carbon material SG as a carbon source, characterized in that: The invention comprises the following components by weight percentage: 0.5-3 parts of sugar-derived carbon material SG and 97-99.5 parts of semi-finished lead paste; the sugar-derived carbon material SG is a carbon material obtained by pyrolyzing sugar and doping with nitrogen; The preparation method of the sugar-derived carbon material SG comprises the following steps: (1) taking sugar and soaking it in an acid solution, washing it with water, drying it, and grinding it to obtain pretreated sugar; (2) mixing the pretreated sugar with ammonium chloride, heating, cooling, and grinding into powder; In step (1), the sugar comprises chitosan; the acid comprises at least one of oxalic acid and hydrochloric acid; The heating temperature in step (2) is 1000-1200° C., and the heating time is 3-4 hours.
2. The negative electrode additive according to claim 1, characterized in that The mass ratio of the sugar to the acid solution in step (1) is 1-3:5; and / or the mass concentration of the acid solution is 2-4%; And / or the soaking time is 1-2h; and / or the drying method is vacuum drying; And / or the drying temperature is 40-60°C, and the drying time is 12-24h.
3. The negative electrode additive according to claim 1, characterized in that: The mass ratio of the pretreated sugar to ammonium chloride in step (2) is 1:0.5-2; and / or the heating temperature is 1000-1200°C and the heating time is 3-4h; And / or the cooling temperature is 40°C or lower.
4. The negative electrode additive according to claim 3, characterized in that: Step (2) also includes, before heating, heating to 200-400°C at a rate of 2-4°C / min and keeping the temperature for 60-120 minutes.
5. The negative electrode additive according to claim 1, characterized in that: The semi-finished lead paste comprises the following components in parts by weight: 0.05-0.1 parts of lignin, 0.2-0.4 parts of humic acid, 0.05-0.2 parts of fiber, 0.5-2.5 parts of barium sulfate and 97-99 parts of lead powder.
6. The negative electrode additive according to claim 5, characterized in that: The fiber includes at least one of polypropylene fiber, polyacrylonitrile fiber, composite conductive fiber, carbon fiber, polyacetylene fiber, polyaniline fiber, polypyrrole fiber and polyester fiber.
7. A lead-carbon battery negative plate, characterized in that: The negative electrode additive comprises any one of claims 1 to 6.
8. The process for preparing the negative electrode plate of a lead-carbon battery according to claim 7, characterized in that: The steps include: S1: mixing the sugar-derived carbon material SG and the semi-finished lead paste, adding water, and stirring to obtain a mixture; S2 is to coat the mixture on the negative electrode grid, flatten it, spray it with acid, solidify it, and dry it.
9. The preparation process according to claim 8, characterized in that: In step S1, the mass ratio of water to sugar-derived carbon material SG is 0.05-0.15:1; step S1 is stirred in a paste mixer; in step S2, sulfuric acid is used for acid showering, and the density of sulfuric acid is 1.23-1.28 g / mL.
Citation Information
Patent Citations
Active material of super lead storage battery plate
CN102024946A
Modified activated carbon with high hydrogen evolution potential and preparation method thereof as well as lead-acid battery negative lead paste containing modified activated carbon
CN102306784A
Preparation method of nitrogen-doped porous carbon foam material and application of nitrogen-doped porous carbon foam material in metal-air battery
CN106356537A
Nitrogen-doped hierarchical porous carbon material for lead-carbon battery and preparation method of nitrogen-doped hierarchical porous carbon material
CN111302326A
Carbonaceous material suitable for negative electrode active material of electricity storage device, negative electrode for electricity storage device, and electricity storage device
CN116210067A